Pengaruh Pemberian Insentif Pajak Terhadap Kepatuhan Wajib Pajak UMKM : (Studi Pada Wajib Pajak UMKM Yang Berada Di Kabupaten Sikka Provinsi Nusa Tenggara Timur) - Maria Angelina Jelita; Yosefina Andia Dekrita; Fransiskus De Romario (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study was to investigate whether tax incentives impact the compliance of MSME taxpayers. It will employ quantitative research methods with a descriptive verification approachto determine the extent ot the influence of tax incentives on MSME taxpayer compliance. The sample in this study was 64 MSME taxpayers. The technique for collecting data involves administering a questionnaire that has undergone rigorous testing to ensure its validity and reliability. The data analysis technique used to answer the hypothesis was simple linear regression. Based on the coefficient of determination test, it’s evident that tax incentives contribute significantly to the compliance of MSME taxpayers with a contribution of 92,5% observed in the data analysis results. Furthermore, the results of testing the hypothesis can be seen that the t-count value was 2,249 and the t-table value was 1.999. The hypothesis testing revealed that the t-count value was higher than the t-table value (2,249 > 1,999). It can be inferred that tax incentives had a positive and significant influence on MSME taxpayer compliance in East Alok, West Alok, and Alok Sub-districts of Sikka Regency.